Exploring Personal Information - Cutrell, Edward; Dumais, Susan; Cutrell, Ed (Communications of the ACM (Special Issue: Supporting Exploratory Search), 2006)
When we look for information in large or unfamiliar sources such as the Web or an encyclopedia, it is almost second nature to use a search engine to help us find what we need. Yet until recently, people have had to be more creative when trying to find information on their own computers; locating an email message, a bank statement, or a short movie clip of a friend on your own computer can be an exercise in patience and luck. While research in the area of personal information access has been ongoing for several years [1, 3], we are only now beginning to see widespread use of such tools. Rich search and browsing capabilities to support exploration are now being built into the next generation of PC operating systems (for example, Apple’s Spotlight for Tiger OS X and Microsoft’s Vista Search) and are also available in a variety of standalone desktop search tools.